Comparative assessment of quality characteristics of Chungkookjang made from soybean seeds differing in oleic acid concentration. (January 2019) - Lee, Dong-Ho; Kulkarni, Krishnanand P.; Kim, Byung-Oh; Seok, Young Mi; Song, Jong Tae; Lee, Jeong-Dong
Graphical abstract: Highlights: The functional characteristics of high-oleic soybean Chungkookjang were assessed. The oleic acid content during Chungkookjang fermentation was not altered. Antioxidant activity was reduced, whereas protease activity was not affected. Isometric tension measurements indicate greater benefits from increased oleic acid. Abstract: Chungkookjang is a beneficial fermented soybean food with anticancer, anti-inflammatory, and antioxidant activities. High oleic acid (HO)-containing diets are known to help in preventing cardiovascular disease (CVD). In the present study, we assessed functional quality characteristics of Chungkookjang made from soybean seeds differing in oleic acid concentration. Chungkookjang made from HO and normal oleic acid (NO) soybeans did not differ significantly in moisture content, pH, viable cell number, protease activity, amino type nitrogen, and polyphenol activity. However, the diphenylpicrylhydrazyl (DPPH)-scavenging activity and flavonoid contents of Chungkookjang made from HO soybeans were lower than those from NO soybeans. The oleic acid concentrations were not significantly altered by fermentation. Additionally, Chungkookjang from the HO soybean cultivar 'Hosim' affected the vascular relaxation of endothelium-intact rat aortic rings at concentrations as low as 0.03 mg/mL. The results showed that Chungkookjang from HO soybeans possesses characteristics that might be potentially helpful in reducing the risk of CVD.